Intrinsically unstructured proteins: regulation and disease - Babu, M. Madan (Henry Stewart Talks, 2012)
Regulatory genomics and systems biology, Intrinsically unstructured proteins (IUPs): structural and biophysical advantage, Functional advantage, Thermodynamic and kinetic advantage, Conformational advantage, Identification of IUPs, Functions of IUPs, Disadvantages of unstructured regions, Unstructured regions in proteins, Cells minimize the risks of unstructured proteins, Tight regulation of IUPs, Key regulatory events affecting protein availability, IUPs in yeast, Gene-ontology functional enrichment analysis, Genome-scale datasets on transcript availability, Transcripts encoding IUPs are tightly controlled, Mechanisms affecting transcript stability, Genome-scale datasets on protein availability, IUPs are tightly controlled at the translational level, PEST sequences, Aggregation prone IUPs: more tightly regulated, Control calculation, Tight regulation of IUPs is evolutionarily conserved, Control of IUP affects signaling fidelity/regulation, Control of specific IUP affects protein aggregation
Reviewed at 2016/11/01